UJI EFEKTIVITAS EKSTRAK DAUN (Piper Betle L.) SIRIH TERHADAP PERKEMBANGAN LARVA AEDES AEGYPTI SP - Sembiring, Firza Khairullah; BT Hasan, Riyani Susan (Universitas Jambi, 2020)
This research was conducted to determine the effectiveness of betel leaf extract conducted at a concentration of 2.5%, 5.0%, 7.5%, 10% as larvicide toward the development of Aedes Aegypti Sp. Aedes Aegypti Sp larvae are dangerous vectors in Dengue Hemorrhagic Fever (DHF) in humans. The method in this research was carried out on an experimental method by using a post-test only design and sampling with a purposive sampling method. The effectiveness of betel leaf extract larvicide on the development of Aedes Aegypti Sp larvae was carried out by mixing betel leaf extract with several concentrations in one container Aedes Aegypti Sp larvae inside. The results obtained in this research were carried out by the Kruskal-Wallis test, the test found that there was a significant difference because it was given a 95% confidence index. The larvae treated with betel leaf extract with a concentration of 10% had the highest effectiveness in stopping the development of Aedes Aegypti Sp larvae, which proved at the mortality at a concentration of 10%, found total mortality of 20 larvae in 8 hours of treatment. Betel leaf extract with a concentration of 10% had the highest effectiveness of discontinuing the development of Aedes Aegypti Sp larvae.